Realism and sociology : anti-foundationalism, ontology, and social research - Cruickshank, Justin, 1969- (Routledge studies in critical realism ;, 2003)
In recent years, methodology debates in the social sciences have increasingly focused on issues relating to epistemology. Realism and Sociology makes an original contribution to the debate.